Targeting Endogenous K-RAS for Degradation through the Affinity-Directed Protein Missile System. Issue 9 (17th September 2020) - Röth, Sascha; Macartney, Thomas J.; Konopacka, Agnieszka; Chan, Kwok-Ho; Zhou, Houjiang; Queisser, Markus A.; Sapkota, Gopal P.
Summary: K-RAS is known as the most frequently mutated oncogene. However, the development of conventional K-RAS inhibitors has been extremely challenging, with a mutation-specific inhibitor reaching clinical trials only recently. Targeted proteolysis has emerged as a new modality in drug discovery to tackle undruggable targets. Our laboratory has developed a system for targeted proteolysis using peptidic high-affinity binders, called "AdPROM." Here, we used CRISPR/Cas9 technology to knock in a GFP tag on the native K-RAS gene in A549 adenocarcinoma (A549 GFPKRAS ) cells and constructed AdPROMs containing high-affinity GFP or H/K-RAS binders. Expression of GFP-targeting AdPROM in A549 GFPKRAS led to robust proteasomal degradation of endogenous GFP-K-RAS, while expression of anti-HRAS-targeting AdPROM in different cell lines resulted in the degradation of both GFP-tagged and untagged K-RAS, and untagged H-RAS. Our findings imply that endogenous RAS proteins can be targeted for proteolysis, supporting the idea of an alternative therapeutic approach to these undruggable targets. Highlights: Generation of A549 cells with a homozygous knockin of GFP tag on the KRAS gene Proteasomal degradation of endogenous GFP-K-RAS using a VHL-GFP-nanobody fusion Proteasomal degradation of endogenous H/K-RAS using VHL-H/K-RAS-monobody fusion Abstract : By using the affinity-directed protein missile (AdPROM) system comprised of VHL and high-affinity binders of GFP and H/K-RAS, Röth et al. demonstrate the targeted proteasomal degradation of GFP-K-RAS, which was knocked in using CRISPR/Cas9, and endogenous H/K-RAS.